PRESENTASI DIRI DAN HYPERREALITAS PADA ERA KENORMALAN BARU PANDEMI COVID-19 DI INDONESIA - Watie, Errika Dwi Setya; Fanani, Fajriannoor (Master of Communication Science Program, Universitas Diponegoro, 2022)
The impact of the ongoing Covid 19 pandemic which entering the beginning of 2021 has leads to changes the way humans interact. Previously interaction was done directly face to face, but now the pandemic forced affected humans to interact more using social media. This condition leads to the question of how the human self looks in it. Is there any changing or not? How they were change? And how it potentially creates a symbolic world with artificial behavior that we knew as hyperreality? The research was conducted using a qualitative descriptive method, with purposive sampling, between March 2020 and August 2020 which was the initial period of pandemic quarantine. It was assume that in this period social media users started to shape their appearance on social media. Based on the results of the conducted research, three types of self-appearance emerged, they were the social interaction appearance; Personal appearance; and Busy appearance. All the types of selfappearance created a world that we knew as hyperreality. In this world, the office workers dedicated themself to be at their best in social media appearance while the reality behavior was not always the same. It then creates a notion that social media appearance were far more important and meaningful then the everyday reality